Culture, Northern Ireland, and the Second World War - Woodward, Guy (Trinity College (Dublin, Ireland). School of English, 2012)
This thesis explores the impact of the Second World War on literature and culture in Northern Ireland between 1939 and 1970. It argues that the war, as a unique interregnum in the history of Northern Ireland, challenged the entrenched political and social makeup of the province and had a profound effect on its cultural life. Critical approaches to Northern Irish literature and culture have often been circumscribed by topographies of partition and sectarianism, and it is striking how the Second World War seems to have created conditions for reconsidering the province within broader European and global contexts.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin.